The Difference of Menstural Pain Reduction between Warm Compress and Back Massage - Yayang Kharistik Almasith; Fresthy Astrika Yunita; Agus Eka Nurma Yunita (Journal of Health Science and Prevention, 2017)
Menstrual pain can reduce activities. A preliminary study showed that 80% of the students of STIKES Aisyiyah Surakarta experienced the menstrual pain. A non-pharmacological intervention to reduce the menstrual pain can be done through the execution of warm compress and back massage. The aim of this study was to investigate the difference of pain reduction between warm compress and back massage on menstrual pain among the students of STIKES Aisyiyah Surakarta. This was a quasy experimental research with the non-randomized control group pretest posttest design. Thirdty students STIKES Aisyiah became the research subject. The result of Paired T Test showed that the mean of warm compress= 2.400, with the p-value= 0.000 was greater than that of back massage= 1.267 with the p-value= 0.002.This indicated that there was a difference between the two methods as the warm compress was more effective than back massage on reducing menstrual pain. In time to come, midwifes should conduct counseling on menstrual pain with natural and safe warm compress.